A Multi-stakeholder Management Perspective For Sustainable Ecotourism In Penang Hill - Salman, Ahmad (2022)
Ecotourism brings economic, cultural and environmental sustainability in the destination. Ecotourism was introduced because of the negative impact of mass tourism on the destination. Ecotourism focuses on learning about nature, landscapes, the environment and the culture. Many destinations struggle to achieve sustainable ecotourism due to the involvement of multiple stakeholders with varying interests and power. Penang Hill, one of the latest inductees to the world biosphere reserve network, also has multiple stakeholders. This study aims to close the knowledge gap in managing stakeholders of the destination by understanding the interests and influence of the stakeholders of Penang Hill. The main objectives of the study focused on exploring the management of Penang Hill, exploring stakeholders perceptions related to stakeholder management and ecotourism sustainability, identify the relationship between stakeholders interests and influence on stakeholder management, assess the relationship between stakeholder management and sustainable ecotourism in Penang Hill and finally to analyse whether stakeholder management mediates the relationship between stakeholders interests and stakeholders influence on sustainable ecotourism in Penang Hill. A mixed-method approach was used in this study. The data was collected concurrently with the help of semi-structured interviews and questionnaire from the key and primary stakeholders of Penang Hill.